DAMPAK INDUSTRI PELEBURAN LOGAM Fe TERHADAP PENCEMARAN DEBU DI UDARA - Teguh Prayudi (Jurnal Teknologi Lingkungan, 2005)
In this research have been done by the iron metal rate analysis (Fe) in air dirtambient industry area molding of metal in Dusun Batur, Kecamatan Ceper,Kabupaten Klaten, Provinsi Jawa Tengah. Research result indicate that thedistribution contamination of metal Fe have extended with swampy forest[among/between] 0,02 ~ 15,71 ug/m3, and this rate enough significant with dirtcontent TSP which are research before all.